'The Way of Abstinence': Stigma and Spirituality in Danshukai, a Japanese Self-help Organisation for Alcoholics. Issue 1 (2nd January 2016) - Chenhall, Richard; Oka, Tomofumi
ABSTRACT: Stigma associated with alcoholism is common in Japan, and individuals who suffer from alcoholism often feel that it is a taboo to discuss their problems with alcohol in the general public. This paper describes the way in which the self-help group called Danshukai offers a model for recovery for people suffering from alcoholism in Japan. Since 2006, the authors have been involved in various meetings and conducted conversational and semi-structured interviews with leaders and rank-and-file members of Danshukai. In Danshukai, recovery is viewed as a spiritual process offering the potential for a new life compared to models offered by medical treatment that place little emphasis on the role of spirituality in recovery. While medical models seek to reduce alcohol-related stigma by viewing it as a treatable 'disease', rather than a personality weakness, Danshukai encourages members to embrace their identity as a Danshukai member and to engage with a 'way of abstinence' that includes a lifelong commitment to Danshukai activities and helping others with similar problems.